1999
DOI: 10.1007/s101200050035
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features of the superficial spreading type of early gastric cancer

Abstract: Abstract:Background. During a 10-year period (1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995), 59 of 538 patients with early gastric cancer (11.0%) had the superficial spreading type of gastric cancer. We attempted to elucidate the clinicopathological features and investigated the influence of those features on surgical procedures and patient prognoses. Methods. These 59 superficial spreading lesions were analyzed with respect to macroscopic type, lymph node (LN) metastasis, recurrent pattern, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 19 publications
1
14
0
2
Order By: Relevance
“…Для поверхностно-распространенно-го рака характерна высокая частота продолженного роста и реци-дивов после лечения и худший прогноз по сравнению с другими типами РРЖ. Большинство исследователей считают адекватным объемом операции для данной формы РРЖ гастрэктомию с ЛАЭ D2 [33].…”
Section: особенности лимфогенного метастазирования и выбор объема лимunclassified
“…Для поверхностно-распространенно-го рака характерна высокая частота продолженного роста и реци-дивов после лечения и худший прогноз по сравнению с другими типами РРЖ. Большинство исследователей считают адекватным объемом операции для данной формы РРЖ гастрэктомию с ЛАЭ D2 [33].…”
Section: особенности лимфогенного метастазирования и выбор объема лимunclassified
“…Endoscopically, despite extensive preoperative examination, determination of the tumor margin is impossible in half of the cases [15]. Japanese authors have suggested the performance of contrast endoscopy, using dye-spraying techniques, and endoscopic clipping of the gastric mucosa by biopsies at intervals of 1 cm [15].…”
Section: Spreadmentioning
confidence: 99%
“…Japanese authors have suggested the performance of contrast endoscopy, using dye-spraying techniques, and endoscopic clipping of the gastric mucosa by biopsies at intervals of 1 cm [15]. However, the extent of resection is usually decided on clinical grounds by the surgeon at operation.…”
Section: Spreadmentioning
confidence: 99%
See 2 more Smart Citations